A Gamified Approach for Learning Elementary Arithmetic Operations - Nurul Amira, Sallik; Irwandi, Hipiny; Hamimah, Ujir (2023)
It is essential for children to learn in a fun and interesting way so that they can maximally absorb difficult concepts in a stress-less manner. With children nowadays being exposed to various interactive digital media types, offline and online, teachers are finding it hard to compete for their focus and attention when using only conventional teaching aids, such as flashcards and posters. We studied a gamified app-based approach for learning elementary mathematical operations to see the effects of its implementation, if any, to young children. The game mechanic involves the player seeking Non-Playable Characters (NPCs) positioned randomly around town to receive game quest(s). Each quest requires the player to solve a simple arithmetic problem (i.e., addition and subtraction) to earn game points. Based on the pre- and post-test's results, we found a statistically significant difference between the mean scores.